Highly depleted Hadean mantle reservoirs in the sources of early Archean arc-like rocks, Isua supracrustal belt, southern West Greenland - Hoffmann, J. Elis; Muenker, Carsten; Polat, Ali; Koenig, Stephan; Mezger, Klaus; Rosing, Minik T. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Growing evidence from the accessible geological record reveals that crust mantle differentiation on Earth started as early as 4.4 Ga. In order to assess the extent of early Archean mantle depletion, we obtained Lu-176-Hf-176, Sm-147-Nd-143, and high field strength element (HFSE) concentration data for the least altered, well characterized boninite-like metabasalts and associated metasedimentary rocks from the Isua supracrustal belt (southern West Greenland). The metasediments exhibit initial epsilon Hf-(3720) values from -0.7 to +1.5 and initial epsilon Nd-(3720) values from +1.6 to +2.1. Initial epsilon Hf-(3720) values of the least altered boninite-like metabasalts span a range from +3.5 to +12.9 and initial epsilon Nd-(3220) values from -0.3 to +3.2. These initial Hf-isotope ratios display coherent trends with SiO2, Al2O3/TiO2 and other relatively immobile elements, indicating contamination via assimilation of enriched components, most likely sediments derived from the earliest crust in the region. This model is also consistent with previously reported initial gamma Os-(3720) values for some of the samples. In addition to the positive epsilon Hf-(3720) values, the least disturbed samples exhibit positive epsilon Nd-(3720) values and a co-variation of epsilon Hf-(3220) and epsilon Nd-(3220) values. Based on these observations, it is argued, that the most depleted samples with initial epsilon Hf-(3220) values of up to +12.9 and high Lu-176/Hf-177 of similar to 0.05 to similar to 0.09 tap a highly depleted mantle source with a long term depletion history in the garnet stability field. High precision high field strength element (HFSE) data obtained for the Isua samples confirm the contamination trend. Even the most primitive samples display negative Nb-Ta anomalies and elevated Nb/Ta, indicating a subduction zone setting and overprint of the depleted mantle sources by felsic melts generated by partial melting of eclogite. Collectively, the data for boninite-like metabasalts support the presence of strongly ...